A dual-role theory of the aspect ratio of the nanofillers for the thermal conductivity of graphene-polymer nanocomposites. (1st March 2021) - Li, Chao; Wang, Jie; Su, Yu
Highlights: The two effects of the aspect ratio studied via an effective-medium theory. The initiation of the graphene thermal networks relies solely on the aspect ratio. The graphene interfacial thermal resistance is highly related to the aspect ratio. There exists an exponential law for the second aspect-ratio effect. The second effect cannot be neglected while the aspect ratio is below 0.01. Abstract: The extremely low thickness-to-length ratio (aspect ratio) of graphene nanofillers has long been considered beneficial to the overall thermal conductivity of graphene-polymer nanocomposites as it creates large surface area and extra channels for phonon transport. From time to time, however, a lower aspect ratio of the nanofillers did not yield a higher thermal conductivity as expected. To explain such phenomena, we explored the dual role played by the aspect ratio of graphene nanofillers in the effective thermal conductivity via an effective-medium approximation based on Maxwell's far-field matching with consideration of imperfect graphene interfaces. On one hand, we found that the initiation of the graphene thermal networks relies solely on the aspect ratio. A lower aspect ratio tends to boost the establishment of the thermal channels. On the other, we discovered a persistent exponential law that relates the graphene interfacial thermal coefficient to the aspect ratio regardless of the matrix material. A lower aspect ratio causes a higher interfacial thermal resistance, thus a possible lower effective thermal conductivity. These two effects are competing against each other in the framework of this theory. The origin of the second effect was discussed and the effect cannot be neglected with an aspect ratio below 0.01. This dual-role theory was confirmed by a large number of experimental observations.